The Interactive Learning Media of Puppet Letters to Stimulate Students' Beginning Reading Skills in Elementary Schools - Rhokhayati Rhokhayati; Slamet Slamet; Matsuri Matsuri (Universitas Pendidikan Ganesha, 2025)
The development of early reading skills constitutes a fundamental foundation in elementary literacy learning. However, early reading instruction is often conducted in a monotonous manner, resulting in limited student engagement and learning motivation. This study aims to explore and analyze students’ learning experiences in developing early reading skills through the use of puppet letter media. The research employed a qualitative approach with a phenomenological design to uncover the meaning of participants’ lived learning experiences. The subjects of this study were a first grade teacher and elementary school students. Data were collected through participatory observation, in-depth interviews, and documentation, using observation and interview guidelines as research instruments. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing to identify the essence of the learning experiences. The findings indicate that the use of puppet letter media enhances students’ enthusiasm, active participation, and self-confidence in recognizing letters, forming syllables, and reading simple words. The medium also supports the creation of an enjoyable and contextual learning environment. The study concludes that integrating culturally based and visually interactive media can serve as an effective strategy to strengthen early literacy. The implications encourage teachers to develop similar creative media to foster more meaningful early reading instruction.